Method of GLIF Model Construction and Implementation - Buchtela, D; Peleska, J; Vesely, A; Zvarova, J (Studies in health technology and informatics, 2005)
Knowledge acquired in medicine is possible to represent by medical guidelines. The most important and nowadays mostly used for formalisation of guidelines is the GLIF (Guideline Interchange Format) model. Final model can be coded in XML (eXtensible Markup Language). Some situations can be modelled only very hard or no ways in a practice use. This paper describes a method of GLIF model construction and implementation in XML. The method specializes in risks of whole process and tries to find a solution to problematical model situations. The GLIF model universality is kept for any medical guidelines.
Keywords: směrnice pro lékařskou praxi jako téma; lidé; Humans; jazyk (prostředek komunikace); Practice Guidelines as Topic; Language